2003
DOI: 10.1051/m2an:2003041
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of total variation flow and its finite element approximations

Abstract: Abstract. We study the gradient flow for the total variation functional, which arises in image processing and geometric applications. We propose a variational inequality weak formulation for the gradient flow, and establish well-posedness of the problem by the energy method. The main idea of our approach is to exploit the relationship between the regularized gradient flow (characterized by a small positive parameter ε, see (1.7)) and the minimal surface flow [21] and the prescribed mean curvature flow [16]. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 25 publications
2
109
0
Order By: Relevance
“…The equivalence to TV regularisation, for instance, can no longer be expected to be true. Feng and Prohl have shown that given a domain Ω ⊂ R N , one can establish, for almost every time t in a given interval (0, T ), strong convergence of a weak solution u β (t) to u(t) in the L p -norm for any p ∈ [1, N/(N − 1)) [8].…”
Section: Regularisation Of the Diffusivitymentioning
confidence: 99%
See 3 more Smart Citations
“…The equivalence to TV regularisation, for instance, can no longer be expected to be true. Feng and Prohl have shown that given a domain Ω ⊂ R N , one can establish, for almost every time t in a given interval (0, T ), strong convergence of a weak solution u β (t) to u(t) in the L p -norm for any p ∈ [1, N/(N − 1)) [8].…”
Section: Regularisation Of the Diffusivitymentioning
confidence: 99%
“…It requires no additional parameters, it is well-posed [3,5,8], scaleinvariant [2], it preserves the shape of some objects [5], and it leads to constant signals in finite time [4]. In [21] it has further been shown that in the space-discrete 1-D case, TV flow with initial data f is equivalent to the so-called TV regularisation [1,6,17], where one minimises the energy functional…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, finite volumes are not suitable for the approximation of the total variation flow: indeed, if a sequence (u k ) k∈N of piecewise constant functions converges to u in L 1 , the total variation of u k does not converge in general to the total variation of u (see Bělík & Luskin (2003) for an example). The total variation flow must be approximated in W 1,1 -conforming discrete spaces, such as P 1 finite element spaces (Bartels, 2012;Feng & Prohl, 2003;Feng et al, 2005). Numerical schemes combining finite volumes and finite element schemes have already been considered for scalar conservation laws with a diffusion term (Feistauer et al, 1999) and for degenerate parabolic equations (Eymard et al, 2006).…”
mentioning
confidence: 99%